Influencing Factor and Challenges in Implementing Knowledge Management System in Higher Education: A Systematic Literature Review - Dion Lamilga Sudiono Sudiono Putra; Rivaldi Rizalul Akhsan; Dana Indra Sensuse; Imairi Eitiveni; Deden Sumirat Hidayat (Eduvest - Journal of Universal Studies, 2026)
In the current digital era, knowledge occupies a strategic position in supporting the performance and sustainability of higher education. The Knowledge Management System (KMS) implementation process plays an important role in driving innovation and increasing efficiency, although it often faces obstacles such as resistance to change and lack of resources. Related studies highlight that strong support from management, a supportive organizational culture, adequate technological infrastructure, and individual capability development are important factors in successful KMS implementation. In this study, a systematic observation of literature methodology was used to collect, assess, and synthesize findings from related publications. Through narrative analysis, this research identifies general patterns and themes regarding the influencing factors and challenges faced in implementing KMS in higher education institutions. The results of the analysis underline the importance of a comprehensive understanding of the supporting factors and existing challenges to enable higher education institutions to develop and implement effective knowledge management strategies. This aims to strengthen innovation and competitiveness of higher education during dynamic global competition. In conclusion, the adoption and implementation of targeted knowledge management strategies is considered crucial for optimizing innovative potential and improving higher education performance in the long term.